The characteristics of HIV patients who are long-term responders to nevirapine - Tenneti, Vijay Seshadri (Curtin University, 2007)
Objective: To define Nevirapine long term responders (NLTRs) and identify the characteristics of patients who stay on the drug for long periods of time without adverse effects and maintain suppression of HIV replication without development of resistance.Methodology: Demographic and clinical data was collected for all the patients >18 years old from Department of Clinical Immunology, Royal Perth Hospital, Western Australia. All the patients included in the study received Nevirapine as part of their first regimen of anti-retroviral therapy. Data collection and analysis were divided in three groups based on their length of stay on Nevirapine; short-term, medium and long-term responders. Patients who stayed on Nevirapine continuously for more than five years were considered long-term responders (60+ months). Patients who withdraw before six months of therapy due to the drug’s side effects or any other reason are considered short-term responders (0-6 months). Patients whose length of stay on the drug is intermediate between these two groups are considered as medium responders (6-60 months). Investigation of the possible genetic influence on response to Nevirapine was made by analysis of genetic markers like HLA-B35+C4, HLA-DR1, and HLA-B14.Results: We found no difference in the frequencies of HLA-DR1 or HLA- B14 in the three groups. However, we found that HLA-B35+HLA-C4 did not occur in any of the Nevirapine long term responders (NLTRs). This was not described in previous studies. Furthermore, when a survival analysis was performed, carriage of HLA-B35+HLA-C4 identified patients who were not NLTRs.Conclusion: This study was carried out to determine whether or not factors like age, gender, baseline CD4+ count, baseline RNA, and HLA alleles would predict the length of stay on Nevirapine. Although the factors considered for the study have previously been associated with hyper-sensitivity reactions, they do not predict how long a patient would stay on the drug. However, it can be understood from the study that patients who had a combination of HLA alleles B35+HLA-C4 would not continue on Nevirapine use for a prolonged time.